Handbook of fillers - Wypych, George (ChemTec ; Plastics Design Library, 2000)
This is a reference of solids capable of changing the physical and chemical properties of materials. Stimulated by the fact that materials can be improved almost beyond recognition by new grades of fillers, this one volume presents the information needed to market, develop, select, manufacture, and apply these versatile materials. Contains the fundamentals and advances in fillers technology and the products in which they are used. The book is divided into three sections. The first is a databank of fillers. The second section is designed to show how material properties can be tailored to the needs of products. Coupled with observations and theories, this section serves to reconcile controversial findings and provides an understanding of the complex issues of filler applications. The last section concentrates on the application of fillers on an industrial scale.